Physiological Roles of Glycogen Synthase Kinase-3: Potential as a Therapeutic Target for Diabetes and Other Disorders - Woodgett, J.R. (Curr Drug Targets Immune Endocr Metabol Disord, 2003)
Glycogen synthase kinase-3 (GSK-3) has perplexed signal transduction researchers since its detection in skeletal muscle 25 years ago. The enzyme confounds most of the rules normally associated with protein kinases in that it exhibits significant activity, even in resting, unstimulated cells. However, the protein is highly regulated and is potently inactivated in response to signals such as insulin and polypeptide growth factors. The enzyme also displays a distinct and unusual preference for substrates that have been previously phosphorylated by other protein kinases which provides obvious opportunities for cross-talk. It’s substrates are diverse and are predominantly interesting regulatory molecules. The molecular cloning of the kinase revealed it to be encoded by two related but distinct genes. Moreover, the mammalian proteins showed remarkable similarity to a fruitfly protein isolated on the basis of its role in cell fate determination. From these humble beginnings, study of the enzyme has accrued further surprises such as its inhibition by lithium, its regulation by serine and tyrosine phosphorylation and its implication in several human disorders including Alzheimers’ disease, bipolar disorder, cancer and diabetes. Most recently, small molecule inhibitors of GSK-3 have been developed and assessed for therapeutic potential in several of models of pathophysiology. The question is whether modulation of such an “involved” enzyme could lead to selective restoration of defects without multiple unwanted side-effects. This review summarizes current knowledge of GSK-3 with respect to its known functions, together with an assessment of its real-life potential as a drug target for chronic conditions such as type 2 diabetes.